COMMUNITY-BASED ECOTOURISM TRAINING FOR CONSERVATION AND INCOME GENERATION - Agus Prasetyo; Yeni Santi; Rahmatiyah Rahmatiyah (JOURNAL OF COMMUNITY DEDICATION, 2025)
Community-based ecotourism development is a strategic approach to integrating environmental conservation efforts with improving the welfare of local communities. This study aims to systematically review the literature related to community-based ecotourism training as a means of conservation and increasing community income. The method used was a literature review of various scientific journals, environmental organization reports, and policy documents related to ecotourism and community empowerment. The study results indicate that participatory ecotourism training can improve conservation knowledge, tourism service skills, and local entrepreneurship opportunities. Furthermore, community involvement in ecotourism planning and management has been shown to increase a sense of ownership of natural resources and strengthen community economic independence. This study recommends the need for synergy between the government, educational institutions, and local communities in designing adaptive and sustainable training programs for community-based ecotourism development.